Can Halal economics make any difference on the happiness of the Nigerian citizenry? (Global Business Management Review (GBMR), 2020)
The petroleum sector is mainstay of the Nigerian economy. This makes the economy suffer sole sector cool feet syndrome. Therefore, the study aimed at ascertaining whether Halal economic system, as alternative system to the on-going system of overdependence on oil sector could improve the Nigeria Happiness. The finding revealed that Nigeria is of course not happy and Halal economic system is a prone opportunity for diversification in the international market place to improve Nigerian happiness. The study conclude that Halal economic system of course is a product of Islamic religious ethics, but the choice and acceptance of its values in the global arena is based more on objectivism and capitalism or globalisation.